Could Expanding and Investing in First-Episode Psychosis Services Prevent Aggressive Behaviour and Violent Crime? - Hodgins, Sheilagh (Frontiers in Psychiatry, 2022)
Objective: Some persons developing, or presenting, schizophrenia engage in aggressive behaviour (AB) and/or criminal offending. Most of these individuals display AB prior to a first episode of psychosis (FEP). In fact, approximately one-third of FEP patients have a history of AB, some additionally display other antisocial behaviours (A+AB). The large majority of these individuals have presented conduct problems since childhood, benefit from clozapine, have extensive treatment needs, and are unlikely to comply with treatment. A smaller sub-group begin to engage in AB as illness onsets. A+AB persists, often for many years in spite of treatment-as-usual, until a victim is seriously harmed. This article proposes providing multi-component treatment programs at FEP in order to prevent aggressive and antisocial behaviours of persons with schizophrenia. Method: Non-systematic reviews of epidemiological studies of AB among persons with schizophrenia, of the defining characteristics of sub-types of persons wih schizophrenia who engage in AB and their responses to treatment, and of FEP service outcomes. Results: Studies have shown that mental health services that simultaneously target schizophrenia and aggressive behaviour are most effective both in reducing psychotic symptoms and aggressive behaviour. Evidence, although not abundant, suggests that a multi-component treatment program that would include the components recommended to treat schizophrenia and cognitive-behavioural interventions to reduce A+AB, and the other factors promoting A+AB such as substance misuse, victimization, and poor recognition of emotions in the faces of others has the potential to effectively treat schizophrenia and reduce A+AB. Patients with a recent onset of AB would require few components of treatment, while those with prior conduct disorder would require all. Such a program of treatment would be long and intense. Conclusions: Trials are needed to test the effectiveness of multi-component treatment programs targeting schizophrenia and A+AB at FEP. Studies are also necessary to determine whether providing such programs in hospitals and/or prisons, with long-term community after-care, and in some cases with court orders to participate in treatment, would enhance effectiveness. Whether investing at FEP would be cost-effective requires investigation.